2020
DOI: 10.20944/preprints202005.0279.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chinese Stock Market Sector Indices Performance in the Time of Novel Coronavirus Pandemic

Abstract: This paper aims to quantify the effect of the deadly novel coronavirus (COVID-19) pandemic outbreak on Chinese stock market performance. Shanghai Stock Exchange Composite Index and its component sector indices are examined in this study. The pandemic is represented by a lockdown dummy, new COVID-19 cases and a dummy for 3 February 2020. First, descriptive analysis is performed on these indices to compare their performances before and during the lockdown period. Next, regression analysis with Exponential Genera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In March 2020, the International Monetary Fund projected that “C'ina's slowdown in the first quarter of 2020 will be substantial and will leave a deep mark for the year” as the Chinese economy sunk to an all-time low in the first 2 months of the year (Hoehl et al, 2020 ). In reality, the Chinese economy dropped 6.8% in the first quarter of 2020 compared to the previous year (Liew and Puah, 2020 ). From the perspective of the stock exchange and indicator of economic growth, the news of the COVID-19 outbreak led Chinese stock markets to fall significantly (Analytica, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In March 2020, the International Monetary Fund projected that “C'ina's slowdown in the first quarter of 2020 will be substantial and will leave a deep mark for the year” as the Chinese economy sunk to an all-time low in the first 2 months of the year (Hoehl et al, 2020 ). In reality, the Chinese economy dropped 6.8% in the first quarter of 2020 compared to the previous year (Liew and Puah, 2020 ). From the perspective of the stock exchange and indicator of economic growth, the news of the COVID-19 outbreak led Chinese stock markets to fall significantly (Analytica, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within a few days after the release, most industries showed overreaction, suggesting a delay in absorbing unusual news. Liew and Puah (2020) also verified that various industries experienced varied levels of lockdown based on their market conditions and business nature.…”
Section: Jakarta Lockdownsmentioning
confidence: 65%
“…Al-Awadhi et al. (2020) and Liew and Puah (2020) also found evidence of a considerable negative effect on the share price of all companies listed on the Shanghai Stock Exchange and the Hang-Seng stock exchange composite index. The IT and pharmaceutical sectors, according to the data, performed better than others throughout the epidemic.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Yilmazkuday (2022) adds to the findings of Baker et al (2020) by demonstrating that a 1% increase in median daily COVID 19 infections in the USA appears to contribute approximately 0:01% of the average fall in the S&P 500 indices on the first day and after one month, the reduction was around 0:03%. Al-Awadhi et al (2020) and Liew and Puah (2020) also found evidence of a considerable negative effect on the share price of all companies listed on the Shanghai Stock Exchange and the Hang-Seng stock exchange composite index. The IT and pharmaceutical sectors, according to the data, performed better than others throughout the epidemic.…”
Section: Capital Markets Response To Covid 19 Pandemicmentioning
confidence: 96%